The role of soaking, steaming, and dehulling on the nutritional quality of Bambara groundnuts (Vigna subterranea (L) Verdc.) - Yahaya, Damba; Seidu, Osman Abdulai; Tiesaah, Charlotte Hazaala; Iddrisu, Musah Baba (Frontiers in Sustainable Food Systems, 2022)
Bambara groundnut (Vigna subterranea (L) Verdc.) is a leguminous plant that is widely cultivated in West Africa for its nutritious seeds. However, the hard-to-cook phenomenon of this legume affects its patronage by consumers. The quality and bioavailability of nutrients are affected by processing techniques during cooking. This study evaluated the effects of processing techniques on the nutritional quality of two Bambara groundnut varieties (namely, Simbi-bile and Sinkpili-zee). For this, each variety was subjected to four processing techniques, namely, (i) dehulled and soaked in water, (ii) dehulled and soaked in 1% NaHCO3 + 1% NaCl, (iii) dehulled and steamed, and (iv) Control. After sample processing, the Association of Official Agricultural Chemists (AOAC) standard protocols were used for chemical analysis. The results on proximate composition, anti-nutritional factors, and seed minerals composition showed significant variations among treatments. The main effects of variety and processing technique markedly influenced the parameters measured. Soaked Bambara groundnut with NaHCO3 reduced anti-nutritional factors. Steamed treatments yielded highest amount of protein (25.87%) while dehulled treated Bambara groundnut produced the highest amount of carbohydrate (42.77%). Calcium, potassium, and iron showed significant reduction (p ≤ 0.05) when dehulled. Additional sodium in processing Bambara increased mineral content of the crop. Anti-nutritional factor levels were also reduced significantly in simbi-bile when soaked. Proximate components (crude protein, crude fat, crude fiber, carbohydrate, and water) had significant changes in their compositions across all the processing techniques. From the correlation analysis, oxalate and phytate have some levels of effect in all varieties on every nutritional or mineral component. Total ash correlated negatively with crude fat and positively with phytate and oxalate. Dehulled and control did not reduce the anti-nutritional factors compared to NaHCO3 + NaCl. From the results, soaking of Bambara groundnuts in 1% NaHCO3 + 1% NaCl prior to cooking was effective in improving nutritional quality while overcoming the hard-to-cook phenomenon. The findings highlight the need to adopt correct processing techniques that conserve the nutritional benefits of these edible seeds. Soaking Bambara groundnut in NaHCO3 + NaCl as a processing technique increases mineral content while reducing anti-nutritional factors, and hence should be adapted.